Language policy in business discourse, ideology and practice - Barakos, Elisabeth (Discourse approaches to politics, society and culture,, 2020)
"Language Policy in Business: Discourse, ideology and practice provides a critical sociolinguistic and discursive understanding of language policy in a minority language context. Focusing on Welsh-English bilingualism in private sector businesses in Wales, the book unpacks the circulating discourses, ideologies and practices of promoting bilingualism as a sociocultural and economic resource in the globalised knowledge economy. It sheds light on businesses as ideological sites for struggles over language revitalisation, which has been characterised by tensions and discursive shifts from essentialist ideologies about language, identity, nation and territory, to an increased commodification of bilingualism. The book is premised on the understanding that language is a focal point for articulating and living out historical power relationships and inequalities, and that language policy processes are never apolitical. It adds to a body of literature about bilingualism in minority language contexts and, more broadly, about how the fields of politics, business and society are inextricably related"--